The wings upon her back - Mills, Samantha (Tachyon Publications LLC, 2024)
"Zenya was a teenager when she ran away from home to join the Mecha God's warrior sect. She was determined to earn her copper wings and protect the people and city she loved. Under the strict tutelage of a mercurial, charismatic leader, Zenya became Winged Zemolai. But after twenty-six years of service, Zemolai is disillusioned with her role as an enforcer in an increasingly fascist state. After one tragic act of mercy, she is cast out and loses everything she worked for. As Zemolai fights for her life, she begins to understand the true nature of her sect, her leader, and the gods themselves."--